Controls or Competition–What's at Issue? - Madden, Carl H. (The Review of Economics and Statistics, 1972)
PpT HE issue is stated that after Phase II the United States faces or competition. Leading economists Charls Walker, Charles Schultze, Murray Weidenbaum and others who oppose controls in principle nevertheless caution (forecast?) against expecting an early return to free markets. The general prescription comes to something like Weidenbaum's: Basically, we need to deal with those concentrations of private economic power which have become insulated from the influences of aggregate monetary and fiscal policy. 1 Charls Walker, Undersecretary of the Treasury, recently predicted voluntary controls for Phase III in a talk before the Manufacturing Chemists Association.2 Walker said this will require what Paul McCracken, former Chairman of the President's Council of Economic Advisers, called a 'social compact'a consensus among business and labor that substantial gains in real economic growth must be paid for by wage and price stability. Arguments supporting such a definition of the issue are grounded in believed about concentration of economic power and concern derived from accepted interpretations of these facts. The evidence concerning these facts will be reviewed in a moment.